New Neotropical Culicoides and redescription of Culicoides reticulatus Lutz (Diptera: Ceratopogonidae) - Santarém, Maria Clara Alves; Da Trindade, Rosimeire Lopes; Da Silva, Tiago Do Nascimento; Castellón, Eloy Guillermo; Patiu, Cátia Antunes De Mello; Felippe-Bauer, Maria Luiza (Zootaxa, 2014)
Seven new species of the Culicoides reticulatus species group are described and illustrated based on specimens from Colombia, Panama and Brazilian states of northern (Amazonas, Pará and Roraima) and southeast region (Rio de Janeiro). The new species are compared with their similar congener, Culicoides reticulatus Lutz, and a systematic key, table with numerical characters to the females of the species are provided. Redescription of Culicoides reticulatus Lutz is given based on type series deposited in the Ceratopogonidae Collection of the Oswaldo Cruz Foundation, Brazil. The distribution of these species is presented in figure 9.